Peningkatan Nilai Ekonomis Masyarakat Poncokomo dengan Memanfaatkan Potensi Pertanian - Sahertian, Pieter; Leondro, Henny (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
Products produced from agricultural businesses such as the cultivation of potatoes, apples, bananas and others play a very important role for the community in Poncokusumo District, Malang Regency. This potential has not been explored and empowered, especially in utilizing agricultural products, land with potential for agro-tourism, and human resources, namely by increasing the knowledge and skills of the Poncokusumo community through the transfer of skills and technology and demonstration plots. The objectives of this program are (1) To increase public awareness as owners of tourist villages; (2) Equipping the community to have skills in processing agricultural products; (3) Provide facilities for displaying processed dry food products and handicrafts; (4) Train the community to have knowledge and skills about business management; (5) Creating online promotion media in the form of Poncokusumo Profile Website and e-commerce Website. To fulfill these objectives, the implementation methods in this community service activity are in the form of; training, practice and coaching as well as guidance. The results achieved from this community service program are: the quality and quantity of processed agricultural products increases, processed products are accommodated in packaging labeled and have PIRT, There is a proper place for displaying processed products, the community has online publication facilities, and there is an increase in product diversification and improvement. community income. Based on the results of the entire series of service activities, it can be concluded that when the community has an understanding as the owner of a tourist village, the willingness to improve skills and knowledge in utilizing their potential turns out to have an impact on increasing economic welfare.